2017
DOI: 10.1007/s13555-017-0208-z
|View full text |Cite|
|
Sign up to set email alerts
|

Certolizumab Pegol in the Treatment of Psoriasis and Psoriatic Arthritis: Preliminary Real-Life Data

Abstract: IntroductionWe present the results of real-life tests conducted in adults affected by psoriatic arthritis (PsA) with mild cutaneous involvement to evaluate the efficacy of certolizumab pegol (CZP), an anti-tumor necrosis factor-alpha agent approved in Europe for the treatment of rheumatoid arthritis and PsA.MethodsAssessments included an evaluation of the Psoriasis Area and Severity Index (PASI) and the Disease Activity Score computed on 44 joints (DAS-44) correlated to the erythrocyte sedimentation rate (ESR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…Certolizumab was generally well tolerated, with infections being the most common AEs (after exclusion of worsening of disease), although none were considered serious. A previous observational study (n = 44) in psoriatic arthritis patients also found no serious infections, 18 and certolizumab phase II-III clinical trials also reported the majority of AEs to be of mild-tomoderate severity. [13][14][15][16] The profile of the most common AEs in this study was slightly different to that of the latter trials, where nasopharyngitis, upper respiratory tract infections and headache were generally the most common AEs.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Certolizumab was generally well tolerated, with infections being the most common AEs (after exclusion of worsening of disease), although none were considered serious. A previous observational study (n = 44) in psoriatic arthritis patients also found no serious infections, 18 and certolizumab phase II-III clinical trials also reported the majority of AEs to be of mild-tomoderate severity. [13][14][15][16] The profile of the most common AEs in this study was slightly different to that of the latter trials, where nasopharyngitis, upper respiratory tract infections and headache were generally the most common AEs.…”
Section: Discussionmentioning
confidence: 65%
“…25 Evidence from two realworld studies further supports the effectiveness of certolizumab for the joint involvement of psoriatic arthritis and the skin component of those with skin involvement/psoriasis. 17,18 Approximately one-third of the certolizumab recipients in the certolizumab phase III clinical trials had previously received biologic therapy. 14,15 It is interesting to note that in this study, a larger proportion of patients [105/153 (69%)] had previously received biologics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features of CZP may be attributable to the PEGylation and the smaller molecular weight, as compared with IFX and ADA. A recent study also additionally showed that CZP monotherapy was an effective and well-tolerated therapeutic alternative for the treatment of psoriasis and psoriatic arthritis, although this study did not discuss the ophthalmic complications [11]. Llorenç et al [12] examined 7 patients with refractory uveitis, 2 of whom had psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In precedent studies finalized to evaluate CZP efficacy on PsA, our group noticed that the drug was effective also on cutaneous involvement 5 …”
Section: Introductionmentioning
confidence: 99%